Human rights and beyond - Dr. Abdulmumini A. Oba (Journal of Islamic Thought and Civilization, 2012)
The world is pluralistic in many ways. It consists of peoples of diverse racial, ethnic, religious, and cultural backgrounds. Several distinct civilizations have emerged from these diverse peoples. The major civilizations in thecontemporary world include Western, Asian, African and Islamic civilizations. With these different civilizations come different ideologies, value systems and worldviews. Although Western civilization has become dominant in the world, Islamic civilization is its major rival. Some have argued that given the fundamental differences between Western and Islamic civilizations, a clash of civilizations is inevitable. This has become apparent particularly in the area of human rights. The international human rights law that emerged in the middle of the last century is dominated by Western thought and historical experience. These human rights lay claim to universality whereas there areconceptual and normative differences between Islamic and Western perspectives of human rights. This paper examines some of the fundamental differences in the concepts and terminologies used in the human rights discourse in Islamic and Western traditions. It also examines the ideological differences affecting their thinking on human rights, and the differences in conceptualizations and methods of enforcing human rights. This paper argues that the values embodied in the Western conception of human rights are not necessarily superior to those of Islam. On the contrary, some are patently inferior. Universal human rights across both civilizations can only emerge in the context of a genuine crosscultural dialogue when the West changes its perceived positional superiority and accepts Islamic civilization as an equal partner in the quest for the protection of the dignity and welfare of humankind.